The anti-apoptosis effect of erythropoietin on neonatal rat cardiocytes during hypoxia/reoxygenation injury and its possible mechanism - Wang, Hua-jun (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2010)
OBJECTIVE: To investigate the anti-apoptosis effect of erythropoietin (EPO) on myocardial cells after hypoxia/reoxygenation in vitro, and the relationship among protein kinase C (PKC), the mitochondrial ATP-sensitive potassium (mitoKATP) channel and EPO in the anti-apoptotic signaling pathways